2006
DOI: 10.1002/pds.1341
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of clinically relevant adverse events from HMG CoA reductase inhibitor trials worldwide from 1982 to present

Abstract: Overall, discontinuation of statin therapy due to adverse events was no worse than placebo. The risks of muscle-related adverse events were in general agreement with the known risks of statins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 137 publications
0
32
0
Order By: Relevance
“…Statin toxicity became of general public interest in 2001, when cerivastatin was withdrawn from the market (52 deaths from rhabdomyolysis) although rhabdomyolysis was not observed in a meta-analysis of cerivastatin clinical trials [15,16]. Such side effects can impair the quality of life, adherence to treatment, and in extreme cases, may lead to death.…”
Section: Statin-related Adverse Effectsmentioning
confidence: 99%
“…Statin toxicity became of general public interest in 2001, when cerivastatin was withdrawn from the market (52 deaths from rhabdomyolysis) although rhabdomyolysis was not observed in a meta-analysis of cerivastatin clinical trials [15,16]. Such side effects can impair the quality of life, adherence to treatment, and in extreme cases, may lead to death.…”
Section: Statin-related Adverse Effectsmentioning
confidence: 99%
“…36 There has not been much difference in muscle symptomatology reported between subjects and controls in large RCTs. 37,38 There may be a tendency to attribute background muscular symptoms to the medication, be it active statin or placebo. This so-called nocebo effect 39 attributes harm to the inactive intervention.…”
Section: Impact Of Statin Myopathy In Exercising Adultsmentioning
confidence: 99%
“…In randomized clinical trials there has been no excess of muscle problems, but placebo-controlled trials have shown 2.5-fold increased risk of myositis defined by 10-fold elevation of CK [22]. The occurrence of myalgia is common complaint in statin-users [21] and can occur without CKelevations [23].…”
Section: Discussionmentioning
confidence: 99%